Comparing Water Treatment Systems in China and Canada: Technologies, Policies, and Historical Contexts - Shu, Rhett Ruide (Transactions on Environment, Energy and Earth Sciences, 2024)
Water treatment is a challenge to every country, given the diversity of its environmental, industrial, and demographic situations. The paper delineates the historical development, technological innovations, and policy frameworks regarding water treatment systems in China and Canada. The huge population and rapid industrialization within China have forced investments in advanced technologies, such as membrane bioreactors and chemical precipitation, for the treatment of industrial pollutants. Contrary to this, in view of its abundant freshwaters, Canada promoted more emphasis on biological treatments, such as constructed wetlands and activated sludge, for the remediation of organic and microbial contaminants. The paper also compares the two countries based on their management of municipal and industrial wastewater, agricultural run-off, and energy sector pollution. The drawbacks, however, are matched to the advantages because although centralized governance can implement large-scale technologies, rurality still lacks such access. The decentralized Canadian system allows room for localized solutions but at the cost of struggling with lax consistency in enforcement and aging infrastructure, especially where Indigenous communities live. This paper provides a comparative analysis to give an insight of how those two countries can learn from each other to improve water management and sustainability on a global level.